Digital Marketing Strategies for Generation Z: An AIDA-Based Case Study of Chatime Indonesia - Siti Syifazalia Anjariska Putri; Meyla Tazqiya Rakhma (Jurnal Spektrum Komunikasi, 2026)
The advancement of digital technology has significantly transformed the marketing landscape, prompting brands to develop communication strategies that are more interactive, personalized, and aligned with the characteristics of today’s consumers, particularly Generation Z. This study aims to analyze the digital marketing communication strategies employed by Chatime Indonesia in engaging Gen Z using the AIDA model (Attention, Interest, Desire, Action) as a conceptual framework. The research adopts a case study method with a descriptive qualitative approach. Data were collected through literature review and documentation of Chatime’s digital content across Instagram, TikTok, and its mobile application during the period of January to July 2025. The findings reveal that Chatime Indonesia implements an inbound marketing strategy through strong visual content, entertaining and relevant storytelling, and interactive loyalty-based application features. These strategies align with Gen Z’s preference for authentic communication, emotional resonance, and meaningful digital experiences. Each stage of the AIDA model is systematically implemented, beginning with capturing attention through visual content, generating interest via relatable narratives, creating desire through personalization and social value, and encouraging action through rewards and app engagement. The study suggests that digital communication strategies should be further developed by expanding meaningful narratives, strengthening collaborations with digital creators, and regularly evaluating audience engagement patterns.